2016
DOI: 10.1364/oe.24.016961
|View full text |Cite
|
Sign up to set email alerts
|

Independent tuning of double plasmonic waves in a free-standing graphene-spacer-grating-spacer-graphene hybrid slab

Abstract: The independent excitation and tuning of double plasmonic waves are realized in a free-standing graphene-spacer-grating-spacer-graphene (GSGSG) hybrid slab, which consists of two graphene field effect transistors placed back-to-back to each other. Resulted from the high transparency and the tight confinement of surface plasmonic mode for the graphene, double plasmonic waves can be independently excited by guided-mode resonances (GMRs). Theoretical and numerical investigations are performed in the mid-infrared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…18 Graphene can achieve ultrawide band tunability by controlling electromagnetic fields or chemical doping due to its semimetal property. 19 A graphene-based split-ring resonator on the SiO 2 / Si substrate has been investigated by Wang et al, showing frequency tunability and amplitude modulation. 20 Dong et al demonstrated a sandwich graphene metamaterial in the THz region that could evaluate the dominant magnetic-vortex toroidal responses.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…18 Graphene can achieve ultrawide band tunability by controlling electromagnetic fields or chemical doping due to its semimetal property. 19 A graphene-based split-ring resonator on the SiO 2 / Si substrate has been investigated by Wang et al, showing frequency tunability and amplitude modulation. 20 Dong et al demonstrated a sandwich graphene metamaterial in the THz region that could evaluate the dominant magnetic-vortex toroidal responses.…”
mentioning
confidence: 99%
“…The rapid development of graphene optoelectronics is expected to make up for this vacancy . Graphene can achieve ultrawide band tunability by controlling electromagnetic fields or chemical doping due to its semimetal property . A graphene-based split-ring resonator on the SiO 2 /Si substrate has been investigated by Wang et al, showing frequency tunability and amplitude modulation .…”
mentioning
confidence: 99%
“…19−26 The Fermi energy of graphene can be modulated conveniently by applying an external voltage, which achieves ultrawideband tunability by controlling electromagnetic fields. 19 Gao et al 20 realized high-contrast, terahertz-wave modulation using gated graphene and based on extraordinary transmission through ring apertures. Wang et al 25 achieved active tuning of the analogue of electromagnetically induced transparency effects by integrating monolayer graphene into all-dielectric metamaterials in THz.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, according to evolving requirements in applications, there is an ever-growing desire for adjustable EOT. Intriguingly, the unique tuning properties of graphene in the THz band have captured widespread attention. The Fermi energy of graphene can be modulated conveniently by applying an external voltage, which achieves ultrawideband tunability by controlling electromagnetic fields . Gao et al realized high-contrast, terahertz-wave modulation using gated graphene and based on extraordinary transmission through ring apertures.…”
Section: Introductionmentioning
confidence: 99%
“…The discovery of a series of new materials, such as graphene, black phosphorus and borophene, have overcome this issue. [18][19][20][21][22][23] The absorption wavelength of the perfect absorber can be dynamically tuned without reoptimizing the geometric parameters of the structure by adjusting its Fermi energy 24) via introducing graphene into the perfect absorber. [25][26][27][28][29][30] Most recently, bulk Dirac semimetals (BDS) have attracted great interest among researchers.…”
mentioning
confidence: 99%